2020
DOI: 10.1038/s42003-020-0864-x
|View full text |Cite
|
Sign up to set email alerts
|

NORFA, long intergenic noncoding RNA, maintains sow fertility by inhibiting granulosa cell death

Abstract: Long intergenic non-coding RNAs (lincRNAs) have been proved to be involved in regulating female reproduction. However, to what extent lincRNAs are involved in ovarian functions and fertility is incompletely understood. Here we show that a lincRNA, NORFA is involved in granulosa cell apoptosis, follicular atresia and sow fertility. We found that NORFA was downregulated during follicular atresia, and inhibited granulosa cell apoptosis. NORFA directly interacted with miR-126 and thereby preventing it from binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 69 publications
7
51
0
Order By: Relevance
“…In vitro assays proved that knockdown of NORFA significantly induced porcine GC apoptosis, impaired the normal morphology and cell viability, and dramatically inhibited E2 synthesis. Interestingly, we also noticed that NFIX, a transcription factor targeting the promoter of NORFA ( Du et al, 2020 ), is dramatically down-regulated in NORFA -reduced porcine GCs, indicating that a positive feedback regulatory network between NORFA and NFIX exists. Apart from the well-known genes, 202 function-unknown DEmRNAs were identified and further research will focus on investigating their functions.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In vitro assays proved that knockdown of NORFA significantly induced porcine GC apoptosis, impaired the normal morphology and cell viability, and dramatically inhibited E2 synthesis. Interestingly, we also noticed that NFIX, a transcription factor targeting the promoter of NORFA ( Du et al, 2020 ), is dramatically down-regulated in NORFA -reduced porcine GCs, indicating that a positive feedback regulatory network between NORFA and NFIX exists. Apart from the well-known genes, 202 function-unknown DEmRNAs were identified and further research will focus on investigating their functions.…”
Section: Discussionmentioning
confidence: 68%
“…The oligonucleotide sequences used in this study were synthesized by GenePharma (Shanghai, China) and listed as follows: NORFA -specific small interfering RNA (siNORFA), 5′-CAG ACA GAU GUG GAU GAA UTT-3′ (Sense), 5′-UGU GGU UGA UGU UGU UGG CTT-3′ (Anti-sense); NC-siRNA (siNC), 5′-UUC UCC GAA CGU GUC ACG UTT-3′ (Sense), 5′-ACG UGA CAC GUU CGG AGA ATT-3′ (Anti-sense). pcDNA3.1- NFIX , the eukaryotic expression vector for porcine NFIX , was constructed in our previous study ( Du et al, 2020 ). For pan-caspase inhibitor treatment, porcine GCs were seeded into six-well cell culture plates for 36 h, and the medium was then replaced with serum-free DMEM/F12 medium for 12 h. Subsequently, Z-VAD-FMK (#MK3270-1MG, MKBio, Shanghai, China), a well-known pan-caspase inhibitor, was added to the medium to a final concentration of 50 μM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovary, SMAD4 and SMAD4-dependent TGF-β signaling pathway have shown to be associated with follicular development, especially follicular atresia, the ultimate fate of most follicular development 27,28 . Indeed, recent reports demonstrated that SMAD4 contributes to follicular atresia through inhibiting granulosa cell (GC) apoptosis, which is the main inducement of follicular atresia 29 . However, the mechanism of SMAD4 regulating GC apoptosis is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several lncRNAs have been identified as regulators of GC apoptosis in mammals. For example, the lncRNA NORFA inhibited granulosa cell apoptosis through regulating miR-126/transforming growth factor- β (TGF- β ) axis [ 12 ]. Knockdown of PVT1 promoted cell proliferation, as well as inhibition of apoptosis of ovarian granulosa cells by regulating miR-17-5p and PTEN [ 28 ].…”
Section: Discussionmentioning
confidence: 99%